Electrochemical Flow-Cell Setup for In Situ X-ray Investigations: I. Cell for SAXS and XAS at Synchrotron Facilities. Issue 10 (5th August 2016) - Binninger, Tobias; Fabbri, Emiliana; Patru, Alexandra; Garganourakis, Marios; Han, Jun; Abbott, Daniel F.; Sereda, Olha; Kötz, Rüdiger; Menzel, Andreas; Nachtegaal, Maarten; Schmidt, Thomas J.
Abstract : An electrochemical three-electrode flow-cell is presented for in situ small-angle X-ray scattering (SAXS) and X-ray absorption spectroscopy (XAS) experiments in transmission mode at synchrotron X-ray sources. The cell also allows for in situ XAS performed in fluorescence mode. Constant experimental conditions, even under moderate gas evolution, are provided by the electrolyte flow with controlled gas saturation. A special configuration of working and counter electrode, respectively, yields low residual ohmic resistance in three-electrode measurements that enables the study of thick porous electrodes of active high surface area materials. The cell proved its functionality and reliability in two studies: First, an in situ anomalous SAXS experiment for the high-potential degradation properties of a Pt/IrO2 -TiO2 catalyst for the oxygen reduction reaction at polymer electrolyte fuel cell cathodes; and second, an in situ XAS study of the electronic state of Ir centers inside an IrO2 -TiO2 catalyst under oxygen evolution conditions.